The role of hepatocyte growth factor/c-mesenchymal to epithelial transition (HGF/c-Met) signaling pathway In Hepatocellular Carcinoma (REVIEW) - Mona A. Abu El-Makarem,; Rania M. Bakri,; Hatem A. Hassan,; Mahmoud G. Ameen,; Alshymaa A. Hassnine,; Islam S. Farahat,; Nehal I. Abbas, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Hepatocellular carcinoma (HCC) is a one of the most common causes of cancer-related deaths, with complex molecular pathogenesis and interactions. Among these, the hepatocyte growth factor (HGF) and its receptor c-Mesenchymal to epithelial transition (c-Met) have garnered attention for their critical roles in liver biology. Under physiological conditions, the HGF/c-Met signaling aids in tissue repair, regeneration, and homeostasis.